Lifetime Analysis of Energy Harvesting Underwater Wireless Sensor Nodes - Erdem, Huseyin Emre; Güngör, Vehbi Çağrı (Institute of Electrical and Electronics Engineers Inc., 2017)
The application of Wireless Sensor Networks (WSNs) in underwater environments poses various challenges. One of the most important problems is the limited lifetime of underwater sensor nodes. Considering how challenging and costly it is to change the batteries of sensor nodes in underwater environments, energy harvesting methods are rendered as a promising solution. In this study, the contributions of energy harvesting via turbine and hydrophone harvesters as well as schedule and trigger driven energy management methods on node lifetime have been analyzed. Performance evaluations have been conducted considering real-life conditions, e.g. flow rates, of Istanbul Bosphorus Strait. © 2017 Elsevier B.V., All rights reserved.
Keywords: Energy Harvesting; Sensor Node Lifetime; Underwater Wireless Sensor Nodes; Sensor Nodes; Signal Processing; Wireless Sensor Networks; Harvesting Methods; Lifetime Analysis; Management Method; Node Lifetime; Underwater Environments; Underwater Sensors; Wireless Sensor Network (Wsns); Wireless Sensor Node; Energy Harvesting